Increase of Cropping Index in Dryland Supported by Groundwater Irrigation - Anshori, Arif; Srihartanto, Eko; Fibrianty, Fibrianty; Suswatiningsih, Tri Endar; Budiarti, Sri Wahyuni; Riyanto, Damasus; Cahyaningrum, Hermawati; Suradal, Suradal (Universitas Sebelas Maret, 2023)
Dryland has the potential to increase agricultural production, by increasing the cropping index. The main problem of dryland is the availability of water which depends on rainfall. Groundwater can be an alternative option to meet the availability of water in the dryland. This study aimed to determine the cropping pattern and increase of cropping index supported by groundwater irrigation in the dryland. The research was conducted in the dryland of Playen, Gunungkidul, Special Region of Yogyakarta, supported by groundwater irrigation. This research used a combination of survey, interview and plot demonstration methods. Surveys and interviews were conducted to determine the condition of cultivation and profit in the first and third growing seasons. The plot demonstration, to increase the rice cropping index from 1 to 2, was applied in the second growing season. The results showed that rice productivity in the first growing season was 5.215 ton ha-1, with a profit of 12,288,000 IDR ha-1 and B/C of 1.28. In the second growing season, Sidenuk productivity was 8.025 ton ha-1, with the dry straw of 8.049 ton ha-1, grain carbon of 3.471 ton ha-1 and straw carbon of 3.723 ton ha-1, higher than those of Situbagendit, but comparable those of Inpari-42, with a profit of 20,700,000 IDR ha-1 and B/C of 1.54. Rice contributed to higher biomass, carbon and profit than groundnut. In the third growing season, groundnut productivity was 2.026 ton ha-1, with a profit of 15,572,000 IDR ha-1 and B/C of 1.78. Groundwater irrigation can support the increase in the cropping index on dryland and intensify agricultural production as well.